FLEXURAL STRENGTH OF COMBINED STEEL-BASALT FIBER REINFORCED POLYMER REINFORCED CONCRETE BEAMS - Mavlonov, Ravshanbek; No‘manova, Soxiba (Techscience uz - Topical Issues of Technical Sciences, 2025)
A total of nine reinforced concrete beams with combined steel and basalt fiber reinforced polymer (BFRP) reinforcement were fabricated and tested to investigate their behavior under flexure. In addition to experimental testing, the performance of these beams was evaluated through numerical analysis. All combined-reinforced beams exhibited failure due to yielding of the steel reinforcement and crushing of the concrete in the compression zone, while the BFRP reinforcement did not fracture. The experimental results of the combined-reinforced beams were compared with those of conventional steel-reinforced concrete beams, and relevant conclusions were drawn.